Tinjauan Yuridis Penyelesaian Sengketa Terhadap Peralihan Hak Milik Atas Tanah Tanpa Akta Hibah ( Suatu studi di Desa Lelekaa Kecamatan Wolasi Kabupaten Konawe Selatan) - Marlin, Marlin; Marwan, Marwan (Al-Mizan (e-Journal), 2025)
This research aims to understand the settlement of disputes over the transfer of property rights to land without a grant deed and to identify the factors that inhibit efforts to resolve such conflicts. This research was conducted using normative-empirical research method using a statutory approach, a conceptual approach, and sociological enforcement. The results of this study show: (1) disputes generally occur because the granting of grants is done orally or only using ordinary letters without legal validity. The absence of a grant deed, as certified by the Official Certifier of Title Deeds (PPAT), renders the ownership status unclear, particularly after the grantor's death. This condition is exacerbated by the low legal awareness of the community and the lack of guidance from related officials; (2) factors inhibiting the settlement of land grant disputes in Lelekaa Village include the community's low understanding of the legality of grant deeds and legal procedures for the transfer of rights. The community tends to rely on oral or written statements without PPAT authorization, which are not legally valid. Other barriers include limited access to legal services, a lack of socialization from the Indonesian National Land Office (BPN) and PPAT, weak village supervision, and the passivity of officials in guiding residents. Irregular documentation and the absence of an ownership database complicate settlements, especially when multiple heirs or overlapping claims are involved.